Tingkat Pengetahuan Ibu Mengenai Penggunaan Vitamin A Di Desa Gulurejo Lendah Kulon Progo - Dwi Hastuti; Nur Alfiyani (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2022)
Abstract Background: The level of maternal knowledge about the use of vitamin A is very lacking, 56.3% of mothers do not know about vitamin A in general, less knowledge about understanding the function of vitamin A, which is 70.4%, knowledge is lacking in understanding the consequences of vitamin A deficiency of 40.8%, and the category of lack in knowing the source of vitamin A is 66.7% Objective: to determine the level of maternal knowledge about the use of vitamin A in Gulurejo Lendah Kulon Progo Village in February 2022 Method: The research method used is analytical observational with a cross-sectional approach and sampling using purposive sampling techniques. The study population was 1,208 people, so the sample used was 100 people. Data collection was carried out through knowledge questionnaires given to respondents, the results of the questionnaires were analyzed using percentage calculations on respondent characteristics, distribution of questionnaire answers and categorizing the level of knowledge, namely good, sufficient, less Results: The results showed respondents with good knowledge 63%, sufficient knowledge 19% and knowledge less 18% Conclusion: Respondents in Gulurejo Village had a good level of knowledge with the majority of respondents aged 29-37 years, high school education and the type of work were mostly housewives